Appeal to the people's court : rethinking law, judging, and punishment - Luizzi, Vincent. (Value Inquiry Book Series, 2018)
In Appeal to the People's Court: Rethinking Law, Judging, and Punishment , Vincent Luizzi turns to the goings on in courts at the lowest level of adjudication for fresh insights for rethinking these basic features of the legal order. In the pragmatic tradition of turning from fixed and unchanging conceptions, the work rejects the view of law as a set of black and white rules, of judging as the mechanical application of law to facts, and of punishment as a necessary, punitive response to crime. The author, a municipal judge and philosophy professor, joins theory and practice to feature the citizen in rethinking these institutions. The work includes a foreword by Richard Hull, special Guest Editor for this volume in Studies in Jurisprudence.